Japanese slang translation technique in Indonesian subtitle anime Asobi Asobase - Salsabila, Faradhiba; Mustaqim, Ilham Hijrah (Japanese Research on Linguistics, Literature, and Culture, 2022)
Asobi Asobe anime shows the phenomenon of translating slang from the otaku group and the language of young people (wakamono kotoba) in Indonesian subtitles. Slang has links to certain social groups in every culture. Slang translation needs to consider the differences between the social situation of the home culture and the target culture. The proper translation technique is needed in order to be able to translate slang from the source language to the target language. This research intends to describe the techniques used in translating Japanese slang terms in the Indonesian subtitles of the Asobi Asobe anime. The types of translation techniques found are adaptation and modulation. Adaptation is found on 9 data, more than modulation found on 2 data. Adaptation is made by matching Japanese slang words with Indonesian colloquial words, while modulation is made when there are no appropriate equivalents for the Japanese slang words in colloquial Indonesian.